PENDEKATAN NEUROSAINS DALAM PERMAINAN TRADISIONAL BOLA BEKEL UNTUK MENGEMBANGKAN MOTORIK HALUS ANAK USIA DINI DI LINGKUNGAN PERUMAHAN SUKARAMI, KOTA BENGKULU - Lestari, Dita; Komaria, Ria; Nisa, Hairatun; Lingga, Apriska Nursa (MERDEKA : Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze the neuroscience approach in the traditional game of “bola bekel” to develop fine motor skills of early childhood in Sukarami Residential Area, Bengkulu City. The research used a qualitative descriptive method through observation, interviews, and documentation with children aged 4–6 years. The results showed that playing bola bekel provides significant stimulation to children’s fine motor development through hand-eye coordination, concentration control, and neural activity related to motor skills. The findings highlight that traditional games can serve as an effective neuroscience-based learning tool for early childhood, especially in non-formal environments such as residential areas.